Zhuangzi on ‘happy fish’ and the limits of human knowledge - L Cantor (Taylor and Francis, 2019)
The “happy fish” passage concluding the “Autumn Floods” chapter of the Classical Chinese text known as the Zhuangzi has traditionally been seen to advance a form of relativism which precludes objectivity. My aim in this paper is to question this view with close reference to the passage itself. I further argue that the central concern of the two philosophical personae in the passage–Zhuangzi and Huizi–is not with the epistemic standards of human judgements (the established view since Hansen, “The Relatively Happy Fish”), but with the more basic problem of species-specific perspectives. On my reading, Zhuangzi’s emphatic positionality in the passage–on the dam, accompanied by his friend Huizi–plausibly suggests a circumspect reflection on the limitedness of human knowledge. It is significant that Zhuangzi’s knowledge of fish happiness is avowedly from a certain place, and not absolute. But there is still a sense in which this view is objective: namely, insofar as it adequately accounts for an inherently human perspective on the world. I call this modest form of relativism ‘Species Relativism’, which, crucially, leaves room for objectivity, even though a fully objective (i.e. absolute) view of the world is not accessible to humans.